Cooperative Reactive Persistent Surveillance Algorithm Using Multiple UAVs Considering Incident Arrivals. Issue 1 (July 2017) - Lee, Suwon; Kim, Youdan
Abstract: A reactive persistent surveillance algorithm using multiple unmanned aerial vehicles in 2D mission space is proposed considering incident arrivals. Overall coverage is accomplished by target based approach. The algorithm considering incident detection and reduction are used to compute probability distribution which is used to determine revisit time. Multi-agent flocking issue is also considered. Numerical simulation is performed to demonstrate the performance of the proposed algorithm. The proposed algorithm is compared to the existing surveillance motion planner in two aspects: overall coverage and mean incident count.